(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2020)
Claiming rights has traditionally meant achieving political and legal recognition of them for human beings throughout history, yet there are still several invisible groups in this objective, one of which is non-human animals. In the context of emerging rights and according to the idea of "moral progress" it is necessary not only to give voice to those people who would still be in the shadows, but also to include in the recognition of rights non-human animals. Thus, from the value of solidarity we must be able to widen the circle of "we" and consequently institutionalize animal rights.